Pharmacists' confidence when providing pharmaceutical care on anticoagulants, a multinational survey - Papastergiou, John; Kheir, Nadir; Ladova, Katerina; Rydant, Silas; De Rango, Fabio; Antoniou, Sotiris; Viola, Reka; Murillo, Maria Dolores; Steurbaut, Stephane; da Costa, Filipa Alves (International journal of clinical pharmacy, 2017)
Background Guidelines on the management of orally anticoagulated patients are continuously evolving, leading to an increased need for pharmacists to be fully integrated in care provision. Objective To identify self-reported gaps in confidence among practicing pharmacists in the area of anticoagulation. Setting Pharmacists in different work settings in different countries. Method Cross-sectional international survey from October 2015 till November 2016 among pharmacists working in different settings to assess their level of confidence when delivering anticoagulants as well as to identify possible educational needs regarding this medication class. Validation of the survey was ensured. Results Responses from 4212 pharmacists originating from 18 countries were obtained. Pharmacists' level of confidence was significantly higher (p < 0.001) when advising patients on vitamin K antagonists (VKAs) versus non-vitamin K antagonists (NOACs). In general, hospital pharmacists displayed higher confidence levels compared to community pharmacists when advising patients on anticoagulation (p < 0.001). Two distinct patterns of confidence levels emerged relating to basic and advanced pharmaceutical care. Confidence levels when providing advanced pharmaceutical care were significantly higher for Oceania and lower for South America (p < 0.005). Conclusions Pharmacists felt more confident in supporting patients receiving VKAs compared to the more recently introduced NOACs. With the increasing use of NOACs and the risks pertaining to anticoagulation therapy, it is essential to invest in education for pharmacists to address their knowledge gaps enabling them to confidently support patients receiving oral anticoagulants.
Keywords: Needs assessment; Humans; lidé středního věku; veřejné lékárenské služby; nemocniční lékárny; farmaceuti; Female; mladý dospělý; dospělí; internacionalita; Internationality; zdraví - znalosti, postoje, praxe; lidé; Education, pharmacy; Adult; ženské pohlaví; Community Pharmacy Services; Male; Middle Aged; Pharmacists; Pharmacy Service, Hospital; Knowledge; Cross-Sectional Studies; Young Adult; průřezové studie; Health Knowledge, Attitudes, Practice; iPACT; mužské pohlaví; antikoagulancia; Anticoagulants